Employee Engagement, Organizational Commitment and Employee Performance: The Mediating Role of Organizational Citizenship Behavior - Mutia Attalia Nizar; Rahayu Mintarti; Susilowati Christin (JPBM (Jurnal Pendidikan Bisnis dan Manajemen), 2022)
This study aims to analyze the role of organizational citizenship behavior as a mediation effect of employee engagement and organizational commitment on employee performance. This research includes quantitative research using questionnaires to collect data. The population in this study were RSIA Puri Bunda Malang employees. The sampling technique used proportional random sampling with a total sample of 119 respondents. The data analysis technique involved SEM-PLS (Structural Equation Modeling-Partial Least Square). The results indicated that employee engagement and organizational commitment had no effect on employee performance, while organizational citizenship behavior significantly can affect employee performance. The results also showed that organizational citizenship behavior can mediate both the effect of employee engagement and organizational commitment to employee performance. It indicates that the attitude of employee engagement and organizational commitment of employees does not affect employee performance. The presence of organizational citizenship behavior will strengthen the effect of employee engagement and organizational commitment on employee performance. Keywords: Employee engagement, Employee performance, Organizational commitment, Organizational citizenship behavior